Perancangan Sistem Informasi Pemesanan Salon Kecantikan Pada Aura Salon Berbasis Website - Viky Fithrotul Qolbi; Lilik Sugiarto; Hadis Turmudi (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Current technological developments greatly affect life, making companies compete in improving product quality, one of which is in the field of marketing. The purpose of making this information system is to use it to improve the quality and service of ordering at Aura salon, which is a company engaged in the service sector. Services at this salon still serve orders via WhatsApp and customers come directly to the salon as well as promotions that are distributed through print media and social media such as WhatsApp, Facebook and Instagram. The results of this study are designing a website-based beauty salon ordering information system which is expected to facilitate ordering services to customers to be more effective and efficient. The information system was designed using UML (Unified Modeling Language) and using qualitative research methods and using observation data collection techniques, interviews and literature study.